UBV photometry of close visual double stars using an area scanner - Hurly, Patrick Rupert (Department of Astronomy, 2016)
A computer-controlled area scanner designed for use on close visual double stars is described. Techniques used in making observations and in subsequent reduction of the data are given. Problems encountered are discussed. Magnitude differences and magnitudes and colours of components are given for 153 bright southern close visual doubles. Separations are given for some of the stars. Absolute magnitudes are calculated for the primaries by several methods. Individual stars are discussed where appropriate. The accuracy of the results is discussed. No significant systematic errors are evident in the results, but systematic errors are present in the results of other authors. Suggestions are made for the future use of conventional photometers, scanners and other techniques in the field of visual double star photometry and astrometry.